EXPLORING THE USE OF THE CANADIAN OCCUPATIONAL PERFORMANCE MEASURE (COPM) IN UKRAINE: DETERMINING THE NEED - Mangusheva, O. O.; Lazarieva, O. B.; Enemark Larsen, A. (Rehabilitation and Recreation, 2024)
Purpose. The goal of the study was to explore the use of the Canadian Occupational Performance Measure (COPM) by occupational therapists in Ukraine and determining the perceived need for the COPM in Ukraine. Methods. A pilot survey was conducted with 213 Ukrainian occupational therapists using Qualtrics. Quantitative and qualitative data were collected and interpreted via descriptive statistics and thematic analysis assessing the therapists’ knowledge of the COPM, frequency of use, perceived benefits, and barriers to its use. Results. Results showed that while 58% of Ukrainian occupational therapists report some usage of the COPM in clinical practice, frequency of use is occasional rather than systemic. Perceived barriers to using the COPM included: lack of knowledge of the COPM and skills to administer it, lack of appreciation of the value of the COPM for clinical practice, time constraints, lack of integration of the COPM into documentation systems and reluctance to using the COPM for fear of being perceived unprofessional by the patients. Despite these challenges, the COPM was evaluated highly (8 out of 10) by the participants. The study also revealed a prevalent use of unauthorized Ukrainian translations of the COPM, with only 13% of therapists using the official translation version. Conclusions. The findings highlight the need for a rigorous, evidence-informed Ukrainian translation of the COPM and additional education of Ukrainian occupational therapists for its competent use. The study suggests that barriers to using the COPM may stem from a lack of understanding of the philosophy of occupation as the key concept of the profession and calls for further research into the use of occupation- and client-focused outcome measures in a medically dominated environment in Ukraine.